Exceptional increase in the creep life of magnesium rare-earth alloys due to localized bond stiffening. Issue 1 (December 2017) - Choudhuri, Deep; Srinivasan, Srivilliputhur; Gibson, Mark; Zheng, Yufeng; Jaeger, David; Fraser, Hamish; Banerjee, Rajarshi
Abstract Several recent papers report spectacular, and unexpected, order of magnitude improvement in creep life of alloys upon adding small amounts of elements like zinc. This microalloying effect raises fundamental questions regarding creep deformation mechanisms. Here, using atomic-scale characterization and first principles calculations, we attribute the 600% increase in creep life in a prototypical Mg–rare earth (RE)–Zn alloy to multiple mechanisms caused by RE–Zn bonding—stabilization of a large volume fraction of strengthening precipitates on slip planes, increase in vacancy diffusion barrier, reduction in activated cross-slip, and enhancement of covalent character and bond strength around Zn solutes along thec -axis of Mg. We report that increased vacancy diffusion barrier, which correlates with the observed 25% increase in interplanar bond stiffness, primarily enhances the high-temperature creep life. Thus, we demonstrate that an approach of local, randomized tailoring of bond stiffness via microalloying enhances creep performance of alloys. Adding very small amounts of zinc to magnesium alloys containing rare earth elements dramatically improves their creep life. Here, the authors use first principles calculations and atomic-scale characterization to show that this is due to stiff covalent bonding of zinc and rare earth elements such as neodymium.